Genome mining, metabolite fractionation, and evaluation of antibiofilm activity of endophytic Priestia megaterium AJ5 against methicillin-resistant Staphylococcus aureus - JEPRI AGUNG PRIYANTO; GENIA SOTYA SINARAWADI; MUHAMMAD EKA PRASTYA; ORHINTA MUTIARA JATI; NISA RACHMANIA; ZETRYANA PUTERI TACHRIM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Priyanto JA, Sinarawadi GS, Prastya ME, Jati OM, Rachmania N, Tachrim ZP. 2025. Genome mining, metabolite fractionation, and evaluation of antibiofilm activity of endophytic Priestia megaterium AJ5 against Methicillin-resistant Staphylococcus aureus. Biodiversitas 26: 2916-2925. Endophytic bacteria, particularly Priestia megaterium, are a source of secondary metabolites that are valuable for medicinal purposes. Therefore, this study aimed to mine the Secondary Metabolite Gene Clusters (SMGCs) within the complete genome of AJ5 strain, fractionate its secondary metabolites, and evaluate its antibiofilm activity against Methicillin-Resistant Staphylococcus aureus (MRSA). The bacterium had a complete genome length of 5,750,510 bp and was closely related to P. megaterium NCTC10342, with an Average Nucleotide Identity (ANI) of 98.37%. AntiSMASH analysis showed that the bacterium possessed 5 types of SMGCs, including Non-Ribosomal Peptide Synthetase (NRPS)-Independent (NI) siderophores, 3 types of terpenes, and type III Polyketide Synthase (PKS). In addition, 2 selected fractions obtained from thin-layer chromatography and column chromatography procedures exhibited strong anti-MRSA activity. F9 and F12 fractions had Minimum Inhibitory Concentrations (MIC) of 117.5 ?g/mL and 180 ?g/mL, respectively. Liquid Chromatography-Mass Spectrometry/Mass Spectrometry (LC-MS/MS) analysis indicated that these 2 fractions contained nigakilactone H, tetratriacontanamine, 2-(p-Anisyl)-5-methyl-1-hexene, and other unidentified compounds. The compounds were also capable of suppressing biofilm formation of MRSA by up to 81.54%±1.80 for the F9 and 77.01%±1.96 for F12 fraction after treatment with 1×MIC. All selected fractions also exhibited eradication activity against established MRSA biofilms up to 79.23±1.96%. In conclusion, this study showed the SMGCs profile and their metabolite products found within the genome of AJ5 strain, as well as its antibiofilm potential against MRSA. The thoroughness of our research process and the validity of our findings suggest that genome-based screening and in vitro assays could significantly accelerate the development of novel anti-MRSA agents.